The Read Feed - Reviews. Issue 4 (2nd October 2019) - Moreno, Heylicken; Parang, Elizabeth; Church, Jill M.; Wilson, Robert T.
Abstract: Elizabeth Parang reviews Guide to Streaming Video Acquisitions ; Jill M. Church reviews Electronic Resources Librarianship: A Practical Guide for Librarians ; Robert T. Wilson reviews Using Digital Analytics for Smart Assessment .